Reversible debugging using program instrumentation. - Shyh-Kwei Chen (IEEE Transactions on software engineering)
Reversible execution has not been fully exploited in symbolic debuggers. Debuggers that can undo instructions usually incur a significant performance penalty during a debugging session. We describe an efficient reversible debugging mechanism based on program instrumentation. The approach enables repetitive debugging sessions with selectable reversible routines and recording modes. Experimental results indicate that the execution penalty can be significantly reduced with moderate code growth